Factors of Atheism as a Challenge to Effective Da’wah: An Analysis and Strategies for their Solution in Contemporary Era - Dr. Aasia Rashid; Dr. Ume Farva (International Research Journal of Arabic and Islamic Studies, 2024)
Atheism is disbelief or lack of belief in a supreme being called God. It is opposed to “Theism” which is a belief in God and a particular religious philosophy. Although Atheism has its roots in ancient Greece; it has become a major philosophy of life after the Renaissance of Europe. Today more than 60% of Europeans consider themselves atheists and now it has become a key feature of the modern world. There is no doubt about the fact that in Muslim World, Atheism is established and widespread due to social media. In many Major cities of the Muslim world especially among the educated segments of society, Atheism is very common. Although, the number of atheists in the Muslim World is too small but it is increasing at an alarming rate. There are many factors that contributed to the rise of atheism in Europe and the same factors are now causing Atheism in the Muslim world. In this paper, a descriptive and analytical method was used to highlight the importance of the topic. Our youngers are inclined towards atheism due to less awareness of Islam. It is recommended that parents and teacher should educate their kids about the religion of Islam.